A Two-Phase Lifetime-Enhancing Method for Hybrid Energy-Harvesting Wireless Sensor Network - Xiong, Yonghua; Chen, Gong; Lu, Manjie; Wan, Xiongbo; Wu, Min; She, Jinhua (IEEE sensors journal, 2020)
A major concern in wireless sensor network (WSN) is how to maximize the network lifetime while maintaining the coverage requirement. Since the energy of sensor node is limited, the network lifetime is extremely restricted. Recent studies have demonstrated that energy harvesting technology can potentially alleviate the energy limitation. This paper focuses on how to increase the network lifetime while satisfying the full target coverage in a novel Hybrid Energy-harvesting Wireless Sensor Network (HEWSN) which comprises both static non-rechargeable sensor nodes and mobile rechargeable ones, and then proposes a Two-phase Lifetime-enhancing Method (TLM). In the first phase, we employ a Multi-Objective Particle Swarm Optimization(MOPSO) algorithm based on adaptive grid for healing coverage hole, which relocates useful mobile rechargeable sensor nodes at optimal locations to meet the full target coverage. In the second phase, we present a Modified Binary multi-objective evolutionary algorithm based on Non-dominated Sorting and Bidirectional Local Search (MBNSBLS) to schedule sensor nodes into non-disjoint subsets working in turn, which helps to extend the network lifetime. Simulations are conducted and the results show that TLM has better performance than other approaches.